Muslim conception of dying and death: an ethico-legal analysis in the context of medical definition of death - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd. Abbas; Mohamed Yunus, Saidatolakma (LexisNexis Malaysia Sdn. Bhd., 2018)
Islam law being a comprehensive code of conduct prescribes a set of ethico-legal guidelines not only to preserve human life but to regulate human sickness, dying and death. Dying in accordance with Islamic rules especially is of paramount significance about which each and every Muslims with an iota of faith in God, human resurrection and afterlife is concerned. The Qur`an, the Sunnah and Muslim jurists sufficiently guide Muslims as to how to handle illness, dying and matter of declaration of someone as legally dead. Nevertheless, in the modern context, in view of the pivotal role of medical intervention to treat illness and manage end-of-life care, adherence to some of the most cherished Islamic ethico-legal doctrines are not only impossible but also have become subject of intense debate. Most importantly, traditional criteria of death, namely the stoppage of heart throb and respiration are considered no more relevant in view of medical definition of death and its conception especially in the case of comatose patients and those in vegetative state in the hospital wards. This paper while dealing with issues of Muslim notion of death and dying, engages with the debate over sufficiency of medical definition of death to be equated with legal death from Islamic legal perspective and argues for its cautious and restricted use only when traditional signs are not plausible to apply.